Effect of angiotensin II type 1 receptor blocker on osteoporotic rat femurs - Donmez, Baris Ozgur; Ozdemir, Semir; Sarikanat, Mehmet; Yaras, Nazmi; Koc, Pinar; Demir, Necdet; Oguz, Nurettin (Springer Heidelberg, 2012)
Background: Osteoblasts and osteoclasts are known to express Ang II type I (AT1) receptor in cell cultures, suggesting the existence of local renin-angiotensin system (RAS) in bone. This study was designed to investigate the effects of losartan as AT1 receptor blocker on ovariectomized rats' femur. Methods: Losartan (5 mg/kg/day) was administered via oral gavage for 8 weeks. Bone mineral density (BMD) was measured using dual energy X-ray absorptiometry, while tensile and three-point bending tests were performed for evaluation of biomechanical properties of bone. The trabecular porosity was analyzed by scanning electron microscopy. Results: There was a significant decrease in BMD values of ovariectomized rats' femurs which were reversed by losartan treatment. According to tensile test results, ultimate tensile strength and strain values of losartan treated ovariectomized rats' femurs increased and decreased, respectively, when compared to that of ovariectomized animals. Losartan treatment also caused a significant recovery in flexural strength and modulus parameters regarding respective control values, which mean losartan treated ovariectomized rats' femur had more force tolerance until break than ovariectomized rats' femur. Quantitative microscopic analysis showed larger trabecular porosity in ovariectomized rats than control rat femurs and it was significantly decreased after losartan treatment. Conclusion: Blockage of AT1 receptor increased strength, mass and trabecular connections of ovariectomized rat femurs. Therefore, it is tempting to speculate that drugs, including AT1 receptor blockers, may be used for the treatment of osteoporosis or reduction of its detrimental effects in the future.
Keywords: osteoporosis; biomechanics; bone; angiotensin; ovariectomy